Effectiveness of Mother- Child educating program on the development of social skills for a pre- school child - Alfadhil, Hend Hussain; Abdh, Badrelden kamal (Journal of Humanities & Social Sciences, 2022)
The study aimed at clarifying the effectiveness of the Mother- Child educating program on the development of the independence skill for preschool children, the study also aimed at revealing the effectiveness of Mother- Child educating program on the development of appropriate social interaction skills, order and discipline of a pre- school child with his family.In addition to the objectives mentioned above; the study also aimed to verifying the relationship between family characteristics (mother's educational level- the size of the family- the order of the child among his family members- the level of monthly income for families) and the development of social skills for a pre- school child.To achieve the objectives of the study, the researcher used the social survey approach, she also relied on two tools for data collection they were: a questionnaire form directed to mothers to analysis the initial data (demographic) for the child and the family which included some mediated variables such as (mother's educational level- the size of the family- the order of the child among his family members- the level of monthly income for families).The second tool was social skills scale for a pre- school child (prepared by the researcher), the researcher distributed the study tools to the community of the study which consisted of three districts in the city of Bridal, and the estimated number of mother within these districts was about 120 mothers, the tools were applied to sixty mothers benefit from the program and another sixty mothers (had the same characteristics of mothers that have been selected as a human field) but did not submit to the program through the Quota Sample which represents all the characteristics of the original community (mediated variables), they are selected with equal ratios through social survey questionnaires for the three districts, after collecting data and analysis it, the results were as follows: The existence of statistically significant differences at the level of 0.01 between the group which submitted to the program and the group which did not submit to the program in the skills of independence, social interaction, order and discipline in favor of the group submitted to the program.
Keywords: mother and child education program; social skills; pre- school child